Ilizarov’s technique: A pioneer’s vision (Nepal Journal of Epidemiology, 2025)
Orthopedic surgery is a surgical discipline which is diverse in nature and requires a high level of skill. Orthopaedic surgery most commonly requires highly specialized surgical teams as well as costly and sophisticated equipment, this is even more true when it comes to the surgical correction of complicated cases such as malunions, bone infections with bone loss etc. The Ilizarov technique is a marvel of orthopaedics which is multifunctional in purpose and can be used to treat a plethora of conditions. One such pioneer of employing the Ilizarov technique in rural and smaller centers was Dr S.M Banerjee in Kalyani, West Bengal, India over 40 years ago.The Ilizarov technique is a highly diverse and multipurpose surgery which allows for the rectification of complex and challenging cases. The ability for a single surgeon to be able to correct a plethora of conditions with the slight modification of the technique is highly valued in resource limited rural settings where the likelihood and means of such patients to reach a tertiary center is near impossible. Although the procedure may be a fraction more costly and does require a dedicated staff, the near endless applicability of the technique offsets these challenges. All rural based orthopaedic surgeons should both be trained and well versed in the Ilizarov method so as to ensure that even the rural populous have access to a better level of care without having to undergo the trauma of being removed from their locality in order to undergo a procedure at a higher institute. With further aid and support from both local and international authorities, the disparities between the rich and poor as well as health inequality can be minimized via the employment of such a technique in the rural setting.